Striatin translocates to the cytosol of apoptotic cells and is proteolytically cleaved in a caspase 3-dependent manner - Moni Nader; Bariaa Khalil; Wejdan Kattuah; Nduna Dzimiri; Dana Bakheet (Heliyon, 2020)
Striatin (STRN) is a multivalent protein holding great therapeutic potentials in view of its interaction with dynamic partners implicated in apoptosis. Although striatin-3 and striatin-4, that share high structural similarities with STRN, have been linked to apoptosis, the dynamics of STRN in apoptotic cells remain unclear. Herein, we report that the amount of STRN (110 kDa) is reduced in apoptotic cells, in response to various chemotherapeutic agents, thereby yielding a major polypeptide fragment at ~65 kDa, and three minor products at lower molecular weights. While STRN siRNA reduced the 65 kDa derivative fragment, the overexpression of a Myc-tagged STRN precipitated a novel fragment that was detected slightly higher than 65 kDa (due to the Myc-DDK tag on the cleaved fragment), confirming the cleavage of STRN during apoptosis. Interestingly, STRN cleavage was abrogated by the general caspase inhibitor Z-VAD.fmk. Cell fractionation revealed that the STRN pool, mainly distributed in the non-cytosolic fragment of naïve cells, translocates to the cytosol where it is proteolytically cleaved during apoptosis. Interestingly, the ectopic expression of caspase 3 in MCF-7 cells (deprived of caspase 3) induced STRN cleavage under apoptotic conditions. Inhibition of caspase 3 (Ac-DEVD-CHO) conferred a dose-dependent protection against the proteolytic cleavage of STRN. Collectively, our data provide cogent proofs that STRN translocates to the cytosol where it undergoes proteolytic cleavage in a caspase 3-dependent manner during apoptosis. Thus, this study projects the cleavage of STRN as a novel marker for apoptosis to serve pharmacological strategies targeting this particular form of cell death.